Who Wins the Olympic Games: Economic Resources and Medal Totals - Bernard, Andrew B.; Busse, Meghan R. (The Review of Economics and Statistics, 2004)
This paper examines determinants of Olympic success at the country level. Does the United States win its fair share of Olympic medals? Why does China win only 6% of the medals even though it has one-fifth of the world's population? We consider the role of population and economic resources in determining medal totals from 1960 to 1996. At the margin, population and income per capita have similar effects, suggesting that both a large population and high per capita GDP are needed to generate high medal totals. We also provide out-of-sample predictions for the 2000 Olympics in Sydney.